PENGETAHUAN BERHUBUNGAN DENGAN TINDAKAN IBU HAMIL DALAM MENGKONSUMSI TABLET ZAT BESI - Naili Rahmawati (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
KNOWLEDGE RELATING TO PREGNANT WOMEN'S ACTIONS IN EATING IRON TABLETS Background: According WHO (World Health Organization), in developing countries there are 40% of maternal deaths related to anemia during pregnancy. The frequency of pregnant women in Indonesia who experience anemia is still very high, namely 63.5% compared to only 6% in America. The number of pregnant women who experience anemia is due to a lack of knowledge of the mother, amounting to 45.6% of pregnant women do not know the consequences of anemia, do not regularly consume Fe tablets, and do not understand how to consume Fe tablets properly. Knowledge is a very important domain in shaping one's actions. Knowledge is one of the factors to create a person’s attitude. Good knowledge about the importance of iron will create a positive attitude towards adherence in consuming iron tablets. Knowledge of the benefits of something can affect the intention to participate in an activity. Knowledge of the benefits and bad consequences of something will create an attitude an intention, then from that attitude an intention will be arisen. The next intention will determine whether the activity will be carried out or not.Purpose: The objective of this study is to determine the correlation of knowledge and actions of pregnant women in consuming iron tablet at the Midwives Independent Practice ‘I’.Methods: This research is a quantitative study with cross sectional approach. Data were collected using primary data. The research was conducted in August - September 2019. The population in this study were pregnant women at Praktik Mandiri Midwife I, as a sample. In this study, some of the pregnant women at the Midwife's Independent Practice I. Sampling was carried out using the accidental sumpling technique as many as 30 people. With the inclusion criteria, they can write, read, understand Indonesian and be in good health. Researchers used primary data, namely data obtained by interviewing a questionnaire instrument. Analysis of the data used in this study consisted of two stages of analysis as follows: univariate analysis. Univariate analysis and analysis of research data were carried out using the Spearman test.Results: The results showed that 97% of pregnant women had good knowledge, 3% of pregnant women with less knowledge, and 100% of pregnant women with positive action in consuming iron tablets. Bivariate analysis using the Spearman test shows that there is a significant relationship between knowledge and actions of pregnant women in consuming iron tablets.Conclusions: There is a significant correlation conclusion between knowledge and actions of pregnant women in consuming iron tablets . To increase the knowledge and actions of pregnant women in consuming iron tablets is required a counseling routinely and incresed distribution of iron tablet through cross program and cross sectoral activities. Suggestion to increase the knowledge of pregnant women in consuming iron tablets, it is necessary to conduct regular counseling by midwives in collaboration with the health center. Keywords: knowledge, actions, pregnant women, iron tablet ABSTRAK Latar Belakang: Menurut WHO (World Health Organization), di negara berkembang terdapat 40 % kematian ibu berkaitan dengan anemia dalam kehamilan. Frekuensi ibu hamil di Indonesia yang mengalami anemia masih sangat tinggi yaitu 63,5% dibandingkan di Amerika hanya 6 %. Banyaknya ibu hamil yang mengalami anemia disebabkan karena kurangnya pengetahuan ibu, sebesar 45,6% ibu hamil tidak mengetahui akibat dari anemia, tidak teratur dalam mengkonsumsi tablet Fe, dan tidak memahami cara mengkonsumsi tablet Fe secara tepat. Pengetahuan merupakan domain yang sangat penting dalam membentuk tindakan seseorang. Pengetahuan adalah salah satu faktor yang membentuk sikap seseorang. Pengetahuan yang baik tentang pentingnya zat besi akan membentuk sikap yang positif terhadap kepatuhan dalam mengkonsumsi tablet zat besi. Pengetahuan tentang manfaat sesuatu hal dapat mempengaruhi niat untuk ikut dalam suatu kegiatan, Pengetahuan akan segi manfaat dan akibat buruk sesuatu hal akan membentuk sikap, kemudian dari sikap itu akan muncul niat. Niat yang selanjutnya akan menentukan apakah kegiatan akan dilakukan atau tidak.Tujuan: Mengetahui Hubungan antara Pengetahuan dengan Tindakan Ibu Hamil dalam mengkonsumsi Tablet Zat Besi di Praktik Mandiri Bidan ‘I’.Metode: Penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross sectional. Data yang dikumpulkan menggunakan data primer. Penelitian dilakukan pada bulan Agustus - September 2019. Populasi dalam penelitian ini adalah ibu hamil di Praktik Mandiri Bidan I, Sampel dalam penelitian ini adalah sebagian dari ibu hamil di Praktik Mandiri Bidan I. Pengambilan sampel dilakukan dengan teknik accidental sumpling sebanyak 30 orang. Dengan kriteria inklusi bisa menulis, membaca, memahami bahasa indonesia dan dalam kondisi sehat. Peneliti menggunakan data primer, yaitu data yang diperoleh dengan wawancara dg instrument kuesioner. Analisis data yang digunakan dalam penelitian ini terdiri dari dua tahapan analisis sebagai berikut: analisis univariat Analisis univariat dan Analisis data penelitian dilakukan dengan menggunakan uji Spearman.Hasil: Hasil penelitian diperoleh 97% ibu hamil memiliki pengetahuan baik, dan 3% ibu hamil dengan pengetahuan kurang, dan 100% ibu hamil dengan tindakan positif dalam mengkonsumsi tablet besi. Analisis bivariat dengan uji spearman diketahui bahwa terdapat hubungan yang bermakna antara pengetahuan dengan tindakan ibu hamil dalam mengkonsumsi tablet zat besi.Kesimpulan : Terdapat hubungan antara pengetahuan dengan tindakan ibu hamil dalam mengkonsumsi tablet besi.Saran Untuk meningkatkan pengetahuan ibu hamil dalam mengkonsumsi tablet zat besi perlu dilakukan penyuluhan secara rutin oleh bidan dengan kerjasama dengan puskesmas. Kata Kunci : pengetahuan, tindakan, ibu hamil, tablet besi